1991
DOI: 10.1007/bf00002358
|View full text |Cite
|
Sign up to set email alerts
|

Spawning behaviour ofCheimerius nufar in captivity

Abstract: SynopsisThe santer Cheimerius nufar is widespread in tropical and subtropical waters of the western Indian Ocean and forms an important component of linefish catches along the east coast of southern Africa. Observations of spawning behaviour in captivity have revealed that spawning occurs during spring over a period of four months. Mating takes place at sunrise and may continue for up to 105 min (mean duration = 60 min). During spawning males become dark with prominent white markings. They become very aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…These indications that presented opportunities consisted of: a) spawning was often in a pair indicating the pair could select each other, b) aggregations brought all the fish together for close contact to aid selection and spawning was often soon after an aggregation, c) males followed females perhaps seeking selection, d) males nudged females to possibly stimulate selection, e) females were observed to swim away from advances from males and f) males changed colour changing appearance to perhaps aid selection by the female. Aggregations and/or courtship behaviours similar to the present study have been described in other species of Sparidae including silver seabream (Chrysophrys auratus) (Smith, 1986;Mylonas et al, 2011), santer seabream (Cheimerius nufar) (Buxton & Garratt, 1990;Garratt, 1991), roman seabream (Chrysoblephus laticeps) (Buxton, 1990), silver bream (Rhabdosargus sarba) (Leu, 1994) and southern black bream (Acanthopagrus butcheri) (Mylonas et al, 2011) and nonSparidae such as the spotted sand bass (Paralabrax maculatofasciatus) (Miller & Allen, 2006), yellowtail amberjack (Seriola lalandi) (Moran et al, 2007), dusky grouper (Epinephelus marginatus) (Zabala et al, 1997), cubera snapper (Lutjanus cyanopterus) (Heyman et al, 2005) and white seabass (Atractoscion nobilis) (Aalbers & Drawbridge, 2008). However, in the present study, aggregations were not always observed immediately prior to gilthead seabream spawning and no inter-individual dominances were observed.…”
Section: Behaviour Descriptionsupporting
confidence: 86%
See 4 more Smart Citations
“…These indications that presented opportunities consisted of: a) spawning was often in a pair indicating the pair could select each other, b) aggregations brought all the fish together for close contact to aid selection and spawning was often soon after an aggregation, c) males followed females perhaps seeking selection, d) males nudged females to possibly stimulate selection, e) females were observed to swim away from advances from males and f) males changed colour changing appearance to perhaps aid selection by the female. Aggregations and/or courtship behaviours similar to the present study have been described in other species of Sparidae including silver seabream (Chrysophrys auratus) (Smith, 1986;Mylonas et al, 2011), santer seabream (Cheimerius nufar) (Buxton & Garratt, 1990;Garratt, 1991), roman seabream (Chrysoblephus laticeps) (Buxton, 1990), silver bream (Rhabdosargus sarba) (Leu, 1994) and southern black bream (Acanthopagrus butcheri) (Mylonas et al, 2011) and nonSparidae such as the spotted sand bass (Paralabrax maculatofasciatus) (Miller & Allen, 2006), yellowtail amberjack (Seriola lalandi) (Moran et al, 2007), dusky grouper (Epinephelus marginatus) (Zabala et al, 1997), cubera snapper (Lutjanus cyanopterus) (Heyman et al, 2005) and white seabass (Atractoscion nobilis) (Aalbers & Drawbridge, 2008). However, in the present study, aggregations were not always observed immediately prior to gilthead seabream spawning and no inter-individual dominances were observed.…”
Section: Behaviour Descriptionsupporting
confidence: 86%
“…The reproductive behaviour was similar to that described for other Sparidae species (Smith, 1986;Buxton, 1990;Buxton & Garratt, 1990;Garratt, 1991;Leu, 1994;Mylonas et al, 2011). Gilthead seabream were observed to form defined aggregations prior to the spawning event and females were observed to make a spawning rush with one or more males that finished with gamete liberation.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations